2019
DOI: 10.1111/pbi.13154
|View full text |Cite
|
Sign up to set email alerts
|

MiR319 mediated salt tolerance by ethylene

Abstract: SummarySalinity‐induced accumulation of certain microRNAs accompanied by gaseous phytohormone ethylene production has been recognized as a mechanism of plant salt tolerance. MicroRNA319 (miR319) has been characterized as an important player in abiotic stress resistance in some C3 plants, such as Arabidopsis thaliana and rice. However, its role in the dedicated biomass plant switchgrass (Panicum virgatum L.), a C4 plant, has not been reported. Here, we show crosstalk between miR319 and ethylene (ET) for increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 65 publications
(122 reference statements)
0
43
0
Order By: Relevance
“…By means of transgenic approaches it was established 9 that miR167 acts as transcriptional regulator in response to bacterial infection (Jodder, Basak, Das & Kundu, 2017) and temperature-induced stress in tomato plants (Jodder et al, 2018). Multiple evidences obtained by both sRNA-sequencing and transgenic approaches, support the role of members of the miR319-family, an ancient miRNA conserved across plant species ranging from mosses to higher plants, as a key modulator of the plant-environment interrelation (at biotic and abiotic level) in monocotyledonous and dicotyledonous species (Bustamante et al, 2018;Liu et al, 2019;Shi et al, 2019;Wu, Qi, Meng & Jin, 2020;Fang et al, 2021;Joshi, Chauhan & Das, 2021). Finally, regarding miR398 and miR408 families, it was recently proposed that these conserved miRNAs, involved in the maintenance of the cooper homeostasis in plants, might be also involved in the systemic signaling of the response to biotic and abiotic stresses (Burkhead et al, 2009;Sanz-Carbonell, Marques, Martinez & Gomez, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…By means of transgenic approaches it was established 9 that miR167 acts as transcriptional regulator in response to bacterial infection (Jodder, Basak, Das & Kundu, 2017) and temperature-induced stress in tomato plants (Jodder et al, 2018). Multiple evidences obtained by both sRNA-sequencing and transgenic approaches, support the role of members of the miR319-family, an ancient miRNA conserved across plant species ranging from mosses to higher plants, as a key modulator of the plant-environment interrelation (at biotic and abiotic level) in monocotyledonous and dicotyledonous species (Bustamante et al, 2018;Liu et al, 2019;Shi et al, 2019;Wu, Qi, Meng & Jin, 2020;Fang et al, 2021;Joshi, Chauhan & Das, 2021). Finally, regarding miR398 and miR408 families, it was recently proposed that these conserved miRNAs, involved in the maintenance of the cooper homeostasis in plants, might be also involved in the systemic signaling of the response to biotic and abiotic stresses (Burkhead et al, 2009;Sanz-Carbonell, Marques, Martinez & Gomez, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Over-expression of miR172c substantially increased the sensitivity of plant roots to salt stress, and the removal of miR172c would decrease the sensitivity of plant roots to salt stress, respectively (Li et al, 2016;Sahito et al, 2017). Osa-miR319a and mi319b positively regulate salt tolerance in creeping bentgrass and swithgrass, respectively (Zhou et al, 2013;Zhou and Luo, 2014;Liu et al, 2019). MiR390 increases LR growth under salt stress via the auxin pathway (He et al, 2018).…”
Section: Functions Of Mirna Under Salt Stressmentioning
confidence: 99%
“…The cbp20 mutant is less sensitive to ethylene, while the MIR319b overexpression line shows hypersensitivity to this hormone [115]. In turn, ethylene biosynthesis and salt tolerance genes are altered in pv-miR319-overexpressing switchgrass (Panicum virgatum) upon ACC treatment, enabling enhanced salt-tolerance [116]. While no research reported direct induction of MIR transcription by ERFs, in petunia (Petunia hybrida), PhERF2 promotes RDR2/6, DCL2 and AGO1 expression to regulate siRNAs biogenesis and induce RNA silencing in response to viral infection [117] (Figure 3).…”
Section: Srnas and Abiotic Stress-related Hormones Abscisic Acid And Ethylenementioning
confidence: 99%